Revenge and Killer Instinct in The Menu (2022) Movie: A Jungian Criticism - Handika, Violita Putri (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
The Menu (2022) movie attracts attention with its psychological thriller genre, directed by Mark Mylod, which tells the story of a luxurious experience in an exclusive restaurant. The aims of this study are to describe the depiction of Julian Slowik's persona and shadow as a Chef shown in the movie, and to analyze the conflict between persona and shadow that influences his extreme actions towards the guests in his restaurant. The data source of this research comes from the movie The Menu (2022), with the data consisting of scene captures and dialog. This research uses a psychoanalytic approach with a focus on Carl Jung's archetypes, specifically the concept of Persona and Shadow. The findings show that the depiction of Chef Slowik's persona includes: the leader, professional, perfectionist, and respectable. On the other hand, his shadow depiction includes: anger, vengeful, desperate, and manipulative. The projection of Chef Slowik's shadow onto the guests reflects the conflict between persona and shadow, which creates inner tension that leads to acts of revenge, as a result of his inability to accept his shadow.